NAVIGATING MODERNITY: HAMKA’S RESPONSES TO THE CHALLENGES OF SECULARISM AND MATERIALISM - Fuad, Ai Fatimah Nur (Jurnal Penelitian Humaniora, 2024)
This article explores Haji Abdul Malik Karim Amrullah (HAMKA)’s conceptualization of modern Sufism and its response to the challenges posed by secularism and materialism. In contemporary discourse, traditional Sufi teachings face increasing scrutiny and adaptation in light of prevailing secular ideologies and materialistic pursuits. Through a comprehensive analysis of HAMKA's writings, speeches, and philosophical perspectives, this research investigates how HAMKA reinterprets traditional Sufi principles to resonate with the realities of the modern world. Emphasizing themes of spirituality, ethics, and social responsibility, HAMKA's modern Sufism offers a compelling framework for navigating the complexities of secularism and materialism while preserving the essence of Sufi wisdom. This study highlights HAMKA's visionary approach to modern Sufism, providing valuable insights into its relevance and significance in contemporary discourse on spirituality and social ethics.